Prevalence of Myopia among Children Attending Pediatrics Ophthalmology Clinic at Ohud Hospital, Medina, Saudi Arabia - Aisha Mohammed Alemam; Mohammed Hamad Aldebasi; Abdulkarem Rehmatullah; Rami Alsaidi; Ishraq Tashkandi (Journal of Ophthalmology)
Introduction. Around half of the visually impaired population has uncorrected refractive errors (URE), and myopia constitutes a high proportion of them. URE should be screened and treated early to prevent long-term complications. The aim of this study was to determine the prevalence of myopia among all patients attending a pediatric outpatient clinic at Ohud Hospital in Medina, Saudi Arabia (KSA). Method. This study was conducted using a convenience sample of all patients attending the clinic (1500 patients) aged between 3 and 14 years, and they were enrolled in the study during the period from May 2017 until September 2017. Result. Of 1215 subjects, only 43 (3.54%) were diagnosed with myopia. Out of the study participants, 56.8% were female and the mean age was 9.7 ± 3.6. Myopia was more prevalent in male participants than female participants (n = 525, 4%, n = 690, 3.1%, p=0.5). Low myopia was the most common form among the screened individuals. The level of myopia was associated with the degree of the strabismus angle. Approximately 22% of patients with myopia had >25° strabismus angle. There was a statistically significant association with both near work indoor and outdoor activities on weekends and the level of myopia. Conclusion. The prevalence of myopia among pediatrics patients in Medina is 3.54%. We hope that the results of this study will contribute to a better understanding of this public health issue in Saudi Arabia in order to implant a strict screening program for early detection and interventions to reduce the risk of further progression of visual impairment.